School Environmental Wellness among Senior High School (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Environmental wellness on campus is important as it enables individuals to understand the interconnectedness between student well-being and the school environment, fostering sustainable practices that enhance the student and school healthiness. However, the researchers observe several instances wherein students do not show care for school orderliness and cleanliness. This study examines the school environmental wellness among the respondents that leads to student-driven campus well-being initiatives. Using a mixed method through quantitative survey, and interviews, and photo documentation, the researchers surveyed 202 Grade 11 and 12 students, who represent the primary users of the school facilities. Weighted mean and standard deviation was used in describing the status of school environmental wellness supported by open-ended interview questions, and photo analysis. Findings reveal that waste management practices of both students and school need improvement because there is lacking waste signage resulting in improper waste management practices. The campus care and sanitation is highly satisfactory inside the school premises. However, many students’ express dissatisfaction and raise concern over inadequate supply of sanitary and hygiene products in lavatories and comfort rooms. The overall building and infrastructure management seem very satisfactory, although specific areas require attention like the comfort room ceilings. This study highlights the need for students to take initiatives in helping improve the school environment, serving as the institution’s support system in this matter. The researchers recommend that students lead simple initiatives to resolve these existing concerns including projects that the student body can implement to improve school environmental wellness, while the school administration will take care of concerns beyond the control of students. In elevating the school's environmental wellness, the students and school must work together.
Keywords: physical school environment; campus wellness; policy recommendation